RIVER DIAGNOSIS, CHANNEL ALTERATIONS AND GLOBAL CHANGE: APPLICATIONS OF THE HYDROGEOMORPHOLOGICAL IHG INDEX - Ollero Ojeda, Alfredo; Ballarín Ferrer, Daniel; García García, Jesús Horacio; Ibisate, Askoa; Mora Mur, Daniel; Sánchez Fabre, Miguel (Geographicalia, 2021)
The hydromorphological diagnosis and assessment of rivers is a necessary procedure aimed to improve the ecological status of rivers affected by notable human impacts. The hydrogeomorphological index IHG was designed 15 years ago for that purpose. Its most updated version and its modality for ephemeral courses (IHG-E) are presented. All applications of the index carried out so far are located, a total of 60 both in Europe and in America. The versatility of the index has been demonstrated by the large variety of waterways in which it has been applied. There are reflections on the employability of the index, the adequacy of the indicators analysed, its criteria and the difficulties of application. It is concluded that, in addition to allowing a hydromorphological evaluation, it turns out to be particularly useful for the identification and assessment of impacts in the river area and, therefore, to define restoration proposals and to assess their effectiveness by a progressive implementation of the index throughout monitoring, identifying where the analysed river is improving.
Keywords: fluvial geomorphology; hydromorphological “hymo” indicators; environmental impact; climate change; river restoration